HIV-1 Transactivator Protein Induces ZO-1 and Neprilysin Dysfunction in Brain Endothelial Cells via the Ras Signaling Pathway. (2nd May 2017) - Jiang, Wenlin; Huang, Wen; Chen, Yanlan; Zou, Min; Peng, Dingyue; Chen, Debing
Abstract : Amyloid beta (A β ) deposition is increased in human immunodeficiency virus-1- (HIV-1-) infected brain, but the mechanisms are not fully understood. The aim of the present study was to evaluate the role of Ras signaling in HIV-1 transactivator protein- (Tat-) induced A β accumulation in human cerebral microvascular endothelial cells (HBEC-5i). Cell viability assay showed that 1  μ g/mL Tat and 20  μ mol/L of the Ras inhibitor farnesylthiosalicylic acid (FTS) had no significant effect on HBEC-5i cell viability after 24 h exposure. Exposure to Tat decreased protein and mRNA levels of zonula occludens- (ZO-) 1 and A β -degrading enzyme neprilysin (NEP) in HBEC-5i cells as determined by western blotting and quantitative real-time polymerase chain reaction. Exposure to Tat also increased transendothelial transfer of A β and intracellular reactive oxygen species (ROS) levels; however, these effects were attenuated by FTS. Collectively, these results suggest that the Ras signaling pathway is involved in HIV-1 Tat-induced changes in ZO-1 and NEP, as well as A β deposition in HBEC-5i cells. FTS partially protects blood-brain barrier (BBB) integrity and inhibits A β accumulation.